STRATEGIC IMPORTANCE OF RARE EARTH ELEMENTS FOR MODERN TECHNOLOGIES AND PROSPECTS OF DOMESTIC DEPOSITS - KURYLO, Mariia; КОSHАRNА Sofiia (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In the context of sustainable development, the reorientation of a wide range of technological industries is an inevitable phenomenon that predetermines the perturbations of the established list of raw materials of strategic importance. Changes in priorities are primarily derived from the transition need to innovative approaches in order to solve old problems and ensure all the needs of modern society. So far, integrating into numerous global economic chains, rare earth elements open up a whole range of new opportunities. Within the study information on the main areas of REE use, its market conditions, existing and projected price dynamics were analyzed and summarized; a systematization of stimulating and restraining factors of REE mineral resource base development according to economic, ecological, geological, resource and technological indicators was also made; the connection of the modern "Green Energy Transition" global strategy with the work intensification rate at potential REE mining objects is traced, arguments regarding the primary need to concentrate efforts on replenishing the market for elements of the cerium group, which includes neodymium and praseodymium are given as well. Based on the results of the study, a conclusion regarding the main factors in the development of the REE market was made, and the most promising areas for geological prospecting and mining implementation on the territory of Ukraine were identified.